Information Life Cycle and Its Computer Support - Dziuba, Dariusz T. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The paper focuses on the concept of the information life-cycle and its characteristics. Both a simplified and an extended models of the information lifecycle are discussed. In addition, a computer-aided Information Life Cycle Management strategy is addressed, including its role in the management of information resources and the optimization of specific stages of the information lifecycle in an organization.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 62-70